Character Education Based On Religius Values (Analysis Study ‎In The Majlis Taklim Dzikir Sholawat Syadziliyah Ta’mirul ‎Islam Surakarta)‎ - Muhammad Yasin (IAIN Salatiga, 2019)
The command to recite shalawat is in Surah al Ahzab verse 56 “Indeed, Allah confers blessing upon the Prophet, and His angels [ask Him to do so], O you who have believed, ask [Allah to confer] blessing upon him and ask [Allah to grant him] peace”. This research was conducted in Majlis Taklim Dzikir Shalawat Syadziliyah Ta'mirul Islam Surakarta, with problems namely First, how is the religious value capable of influencing the behavior of the former thugs in the Majlis Taklim Dzikir Shalawat Syadziliyah? Second, what is the strategy of da'wah carried out by the Kyai for former thugs in the Majlis Taklim Dzikir Shalawat Syadziliyah? Third, how does the phenomenon of change experienced by former thugs after following Majlis Taklim Dzikir Shalawat Syadziliyah? The first research objective was to find out religious values that could influence the behavior of former thugs in the Majlis Taklim Dzikir Shalawat Syadziliyah. The second was to find out the strategy of da'wah carried out by Kyai for former thugs in Majlis Taklim Dzikir Shalawat Syadziliyah. This type of research was a qualitative with descriptive approach, while the informants used were in the form of qualitative, the approach used was character analysis and discourse by using interview method and (1) data in the form of natural setting, (2) sampling determined purposively, (3) researcher as a key instrument in collecting and interpreting data, (4) inductive data analysis, and (5) meaning as an essential thing.